Le tourisme tunisien avant et après la Covid-19 - Mohamed Hellal (Études Caribéennes)
In Tunisia, the exploitation of the sun and the shores, for nearly 6 decades, has generated a spectacular development of the mass seaside hotel industry. This mono-activity has been responsible for the current tourism crisis in all its dimensions: economic, social and environmental. The political instability that followed the 2011 revolution, as well as the attacks that hit Tunisia in 2015, have drastically reduced tourist numbers in the country. These political and security crises have been caught up in its recovery by the COVID-19. In fact, the pandemic context would have served as an indicator and gas pedal of the development of a "sustainable tourism" in place of the mass tourism of the preCOVID.